Enhancing fibre-optic distributed acoustic sensing capabilities with blind near-field array signal processing - Muñoz, Felipe; Soto, Marcelo A. (Nature communications, 2022)
Distributed acoustic sensors (DAS) can monitor mechanical vibrations along thousands independent locations using an optical fibre. The measured acoustic waveform highly varies along the sensing fibre due to the intrinsic uneven DAS longitudinal response and distortions originated during mechanical wave propagation. Here, we propose a fully blind method based on near-field acoustic array processing that considers the nonuniform response of DAS channels and can be used with any optical fibre positioning geometry having angular diversity. With no source and fibre location information, the method can reduce signal distortions and provide relevant signal-to-noise ratio enhancement through sparse beamforming spatial filtering. The method also allows the localisation of the two-dimensional spatial coordinates of acoustic sources, requiring no specific fibre installation design. The method offers distributed analysis capabilities of the entire acoustic field outside the sensing fibre, enabling DAS systems to characterise vibration sources placed in areas far from the optical fibre. Here, the authors demonstrate a blind and sparse near-field array signal processing approach to enhance the measurement quality of fibre-optic distributed acoustic sensors. It further enables the accurate estimation of the spatial coordinates of acoustic sources.